Case Report: A case of ectopic tooth with fungal infection in the maxillary sinus - Shumin, Zhao; Qiuliang, Zhao (Frontiers in Surgery, 2025)
This paper reports a case of a maxillary sinus ectopic tooth with fungal infection admitted to the Department of Otorhinolaryngology and Head and Neck Surgery, Affiliated Central Hospital of Shandong First Medical University. The patient, a 74-year-old female, was admitted due to a sensation of “head tightness” and underwent endoscopic resection of the left maxillary sinus open lesion and anterior lacrimal recess approach for maxillary sinus ectopic tooth, with good postoperative results.